Prevención Del Dolor De Dorso Y Manejo Adecuado De Los Equinos De La Vereda El Verjón De Bogotá (2024)
Horses and mules are sentient beings that can show signs of pain or discomfort, which may manifest as a rejection of exercise, lameness, or back pain due to excess weight that can lead to limited mobility, as well as changes in their facial expressions observed in their ears, eyes, and lips. Therefore, it is important to know how to identify and interpret these signs in order to provide appropriate management.